41.7k views
2 votes
If f(x) = x+4 and g(x) =x^3, what is (g•f)(-3)

If f(x) = x+4 and g(x) =x^3, what is (g•f)(-3)-example-1

2 Answers

2 votes

Answer:

The answer is 1

If f(x) = x+4 and g(x) =x^3, what is (g•f)(-3)-example-1
User Souravlahoti
by
5.2k points
5 votes

ANSWER


(g\circ f)( - 3) = 1

Step-by-step explanation

The given functions are


f(x) = x + 4

and


g(x) = {x}^(3)

The composite function,


(g\circ f)(x) = g(f(x))


(g\circ f)(x) = g(x + 4)


(g\circ f)(x) = ( {x + 4)}^(3)

We now substitute x=-3 to obtain:


(g\circ f)( - 3) = ( { - 3 + 4)}^(3)


(g\circ f)( - 3) = ( {1)}^(3) = 1

User Tofuw
by
6.7k points